Respuesta :

Answer:

a) x =18

b) x=2

c) x=3

Step-by-step explanation:

Step(i):-

a)

Given that [tex](x-2)^{\frac{1}{4} }[/tex]

     put x = 18

   ⇒    [tex](18-2)^{\frac{1}{4} } = (2^{4} )^{\frac{1}{4} } = 2[/tex]

      [tex](x-2)^{\frac{1}{4} }[/tex] =2    

b)

put x= 2

[tex](1-x)^{\frac{1}{3} } = (1-2)^{\frac{1}{3} } = (-1)^{\frac{1}{3} } = -1[/tex]

 [tex](1-x)^{\frac{1}{3} } = -1[/tex]

c)

put x=3

[tex]\sqrt{x^{2} +7} = \sqrt{3^{2} +7} = \sqrt{16} = 4[/tex]

[tex]\sqrt{x^{2} +7}= 4[/tex]